Perdas na colheita e qualidade da fibra de cultivares de algodão adensado em função de sistemas de colheita - Ferreira, Francielle Morelli [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Escolhas no manejo cultural tais como sistema de produção e sistema de colheita podem influenciar os índices de perdas na colheita além dos parâmetros de qualidade da fibra, uma vez que, estes fatores, podem ocasionar reduções na qualidade do produto final. Nesse contexto, o objetivo do trabalho foi avaliar a produtividade de cultivares de algodão em sistema adensado, bem como as perdas na colheita e as características da fibra em função dos sistemas colhedores picker e stripper. O experimento foi conduzido na safra de 2012, com espaçamento de 0,45 m, no campo de produção da Fazenda Mirandópolis, município de Juscimeira - MT. Utilizou-se o delineamento em blocos casualizados (DBC). Para as características produtivas do algodão foram considerados apenas dois tratamentos, ou seja, duas cultivares (FMT 701 e IMACD 408), com doze repetições. Para as variáveis relacionadas a perdas na colheita e desempenho operacional das colhedoras utilizou-se DBC em esquema de parcelas subdivididas com dois fatores, sendo, fator A nas parcelas (duas cultivares) e fator B nas subparcelas (dois sistemas de colheita – picker e stripper), com seis repetições. Finalmente, para as características da fibra foram considerados dois níveis para o fator A (duas cultivares) e três níveis para o fator B, ou seja, três sistemas de colheita (sistema manual, sistema picker e sistema stripper), com seis repetições. Avaliou-se a produtividade coletando-se...

Cultural choices in handling such as production system and harvest system can influence the indexes of harvest losses in beyond the fiber quality parameters, since these factors may cause reductions in the quality of the final product. In this context, the objective of this study was to evaluate the yield of cultivars in narrow row cotton system, as well as crop losses and fiber characteristics in function of harvester systems picker and stripper. The experiment was conducted in 2012, with row spacing of 0.45 m, in Mirandopolis Farm, in Juscimeira – MT. Was used a randomized block design (RBD). For cotton productive characteristics were considered only two treatments, in other words, two cultivars (FMT 701 and IMACD 408), with twelve replications. For the variables related to crop losses and operational performance of harvesters was used DBC in split-plot scheme with two factors being the factor A in the plots (two cultivars) and factor B in subplots (two harvesting systems - picker and stripper ) with six replications. Finally, for fiber characteristics were considered two levels of factor A (two cultivars) and three levels for factor B, so three harvesting systems (manual system, picker system and stripper system) with six replications. Was evaluated productivity manually collecting all cotton present in the plant and soon after harvest proceeded to collect the losses in soil and plant. The quality of the fiber was determined in samples collected manually of the plant and after harvest, withdrawn inside the storer basket of each harvester. The analysis of the characteristics the fiber, were analyzed in Laboratory of Classification of Fiber in apparatus by HVI (High Volume Instrument). Losses in soil, plant and total losses did not differ between cultivars, however, for harvest systems, the higher total loss was observed in the picker... (Complete abstract click electronic access below)
Keywords: Produtividade agrícola; Algodão - Cultivares; Fibras - Algodão; Máquinas agrícolas; Cotton